Agricultural Markets in Benin and Malawi - Fafchamps, M; Gabre-Madhin, E (GPRG, 2006)
Based on original trader surveys, this paper examines how agricultural traders operate in Benin and Malawi. Results indicate that the largest transactions costs are search and transport. The use modern technology is limited. Search methods rely principally on personal visits by the trader. Quality control requires the presence of the trader at the time of purchase. This raises costs as the trader has to travel a lot, and makes it di¢ cult for trading enterprises to grow. Since enterprises remain very small, personal transport and search time represents a non-negligible share of marketing costs.